Pengaruh Pembelajaran Matematika Berbasis Masalah untuk Anak Usia 5–6 Tahun TK Negeri Pembina Kihajar Dewantara Kota Selatan - Mita Sari; Adelia Putri Abas; Nayla Faradilla; Haryanti Huna; Naysila Napulo; Putri Alya Suleman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The purpose of this study was to examine how problem-based mathematics learning affected the learning interest of 5- to 6-year-old students at the Ki Hajar Dewantara State Kindergarten in South Jakarta. To compare problem-based mathematics learning and conventional learning, this study used a quantitative method and a quasi-experimental design. Problem-based learning is intended to use mathematical problems in children's daily lives. Children in group B were divided into experimental and control groups. To collect data, structured observations were conducted on elements of children's interest in learning. These included enjoyment, focus, activity, and willingness to participate in learning activities. To determine the difference in the level of interest in learning between the two groups, the data obtained was analyzed statistically. The results showed that, compared to conventional learning, problem-based mathematics learning had a significant effect on increasing children's interest in learning. Children showed more enthusiasm, better concentration, active involvement in activities, and critical thinking skills in solving mathematical problems. The results showed that effective problem-based mathematics learning made learning meaningful, enjoyable, and appropriate for the characteristics of early childhood development.